The effect of genotypes, histidine, NPK fertilizer, cultivars, seasons and their interactions on the physiological growth parameters of flax crop Linum usitatissimum. L (Samarra Journal of Pure and Applied Science, 2023)
A field experiment was conducted during the winter seasons 2020-2021 and 2021-2022 on a private farm in the village of Banat Al-Hassan, southeast of Samarra, in gypsum soil.  The experiment included 180 experimental units with 45 treatments with three replications resulting from the overlapping of compound fertilizer with four concentrations (0, 80, 160, 240) kg. Donum-1 and the amino acid histidine at concentrations of (0, 50, 100) mg L-1 and five genotypes (Local, Sakha 8, Sakha 10, Sakha 12, Giza 8).  The compound and the amino acid histidine.  Factorial experiment within the major and minor fragment plots.  NPK levels were distributed in the major plots and histidine concentrations in the minor plots.  Flax cultivars were distributed in the secondary plots within coefficients multiplied by three replicates using Dunkin' multiple range test at a probability level of 0.05.  The data were collectively analyzed for the effect of seasons.  The results showed that the highest average of dry matter physiological characteristics was 134.16, the highest average net photosynthesis was 15.26, the absolute growth rate 1.05, the relative growth rate 0.034, and the survival time.  The area of ​​the sheet was 114.61